Growth faltering in early infancy: Highlights from a two-day scientific consultation - Aneja, Satinder; Kumar, Praveen; Choudhary, Tarun Shankar; Srivastava, Akanksha; Menon, Purnima (BMC, 2020)
Faltering of growth in early life has been recognized as a public health challenge among Indian babies. A two-day consultation on growth faltering in early infancy was organized to examine the data and evidence on identification and management of early growth failure and to identify knowledge gaps and future areas of research. The consultation was supported by the Biotechnology Industry Research Assistance Council (BIRAC), the Indian Academy of Pediatrics (Nutrition Chapter), Vardhman Mahavir Medical College and Safdarjung Hospital, and the Society for Applied Studies. It brought together researchers, clinicians, policy makers and program managers.